The Effectiveness of Canva Power Point Quiz Media to Improve Reading and Listening Skills - Nafha Sepani; Agus Triyogo (Teaching and General Education Studies, 2025)
This study aims to examine the effectiveness of Canva PowerPoint-based quiz media in improving reading and listening skills of first semester students of the English Education Study Program at PGRI Silampari University. The quiz media uploaded through a blog was designed to combine visual and interactive elements to create a more engaging learning experience. The results showed that 80% of students felt the method was effective in improving their reading skills, while 60% reported improved listening skills. In addition, the majority of students stated that the quiz media helped them understand weaknesses, increase motivation to learn, and build confidence. This study concludes that Canva PowerPoint-based quiz media is effective and can be a useful interactive learning strategy. Further research is needed to test the effectiveness of this media on other language skills and on a wider scale.